Development of antioxidant food packaging materials containing eugenol for extending display life of fresh beef. (November 2018) - Navikaite-Snipaitiene, Vesta; Ivanauskas, Liudas; Jakstas, Valdas; Rüegg, Nadine; Rutkaite, Ramune; Wolfram, Evelyn; Yildirim, Selçuk
Abstract: In this study, clove essential oil (CL) or eugenol (EU) containing cellulose acetate (CA) or acrylic component/hydrophobically modified starch (AC/S) coatings on corona treated oriented polypropylene film (OPP) were designed and investigated for their possible applications as antioxidant packaging materials for fresh meat. The antioxidant properties of the coatings were investigated by Vapour Phase-DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. The CA coatings containing CL or EU showed 43–92% and 43–94% inhibition against DPPH free radicals through the vapour phase, respectively, whereas AC/S/CL and AC/S/EU coatings resulted in DPPH inhibition of 21–65% and 25–84%, respectively. AC/S/EU and CA/EU coatings on OPP containing from 0.32 ± 0.03 to 6.40 ± 0.14 g/m 2 of EU were used to prepare packaging for fresh beef (Longissimus thoracis) . After 14 days, the lipid oxidation in beef steaks kept in control and antioxidant packages was 3.33 and 1.00–1.22 mg of malondialdehyde per kilogram of meat, respectively. Moreover, red colour of beef in antioxidant packages was retained. Highlights: Coatings containing clove essential oil and eugenol on polypropylene film were designed. The antioxidant properties of coatings were investigated through the vapour phase. Eugenol inhibited lipid oxidation in fresh beef and increased its display life.